Moonbeams, dumplings & dragon boats : a treasury of Chinese holiday tales, activities & recipes - Simonds, Nina (Harcourt, Inc., 2002)
Presents background information, related tales, and activities for celebrating five Chinese festivals--Chinese New Year, the Lantern Festival, Qing Ming, the Dragon Boat Festival, and the Moon Festival.